2015
DOI: 10.1007/s00404-015-3654-9
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD44 concentration in the serum and peritoneal fluid samples of patients with different stages of endometriosis

Abstract: The results of this study show that a high expression of sCD44 is correlated with advanced stages of endometriosis. It is also concluded that the detection of serum and/or peritoneal fluid sCD44 may be useful in classifying endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Similarly, HCAM (also referred as CD44) is upregulated in endometriosis tissue, and inhibition of HCAM glycosylation decreases endometrial cell attachment to peritoneal mesothelial cells . Furthermore, higher levels of the soluble form of HCAM in sera and pelvic fluids were found in patients with endometriosis . These observations suggest that both ICAM‐1 and HCAM may play critical roles in the pathogenesis of endometriosis.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, HCAM (also referred as CD44) is upregulated in endometriosis tissue, and inhibition of HCAM glycosylation decreases endometrial cell attachment to peritoneal mesothelial cells . Furthermore, higher levels of the soluble form of HCAM in sera and pelvic fluids were found in patients with endometriosis . These observations suggest that both ICAM‐1 and HCAM may play critical roles in the pathogenesis of endometriosis.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, although the mechanism remains unclear, CD44 and HA are both correlated with drug resistance [10]. Overall, CD44 is a potential prognostic marker for various diseases [48][49][50].…”
Section: Discussionmentioning
confidence: 98%
“…90 Recently, it was observed that sCD44 increases in hepatic steatosis 91 and chronic and aggressive periodontal disease, 92 and its levels correlate with the evolution of endometriosis. 93 One study analyzed sEpCAM in endometriosis, and did not find any correlation. 94 Thus, the soluble forms of these adhesion molecules suffer significant changes in other pathological conditions besides cancer.…”
Section: Hematological Malignanciesmentioning
confidence: 98%